2019
DOI: 10.1186/s12906-018-2427-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of diabetic wound healing by topical application of Vicenin-2 hydrocolloid film on Sprague Dawley rats

Abstract: BackgroundImpaired wound healing is a debilitating complication of diabetes that leads to significant morbidity, particularly foot ulcers. The risk of developing diabetic foot ulcers for diabetic patients is 15% over their lifetime and approximately 85% of limb amputations is caused by non–healing ulcers. Unhealed, gangrenous wounds destroy the structural integrity of the skin, which acts as a protective barrier that prevents the invasion of external noxious agents into the body. Vicenin-2 (VCN-2) has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 64 publications
9
77
0
Order By: Relevance
“…These results have led us to suggest that myricetin accelerates the switch from inflammatory to anti-inflammatory responses, which promotes curing. These findings are consistent with other studies showing increased levels of TNF- α and IL-1 β in serum rats after a burn-injury [ 24 , 25 ].…”
Section: Resultssupporting
confidence: 93%
“…These results have led us to suggest that myricetin accelerates the switch from inflammatory to anti-inflammatory responses, which promotes curing. These findings are consistent with other studies showing increased levels of TNF- α and IL-1 β in serum rats after a burn-injury [ 24 , 25 ].…”
Section: Resultssupporting
confidence: 93%
“…It can be envisaged that the total aggregate effects of all these active components are unique and may act in synergism to accelerate wound and diabetic ulcer healing processes (Al-Hassan, 1990;Zheng et al, 2018). The current study paves the way for making potent therapeutic formulations with minimal number of stable active ingredients for wound healing (Gomes et al, 2017;Tan et al, 2019)or wound dressing applications (Zhao et al, 2017;Qu et al, 2018;.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, active compounds pass penetration through the transappendageal route (sweat glands, hair follicles and sebaceous glands which include open channels on the outside surface of the skin) [57,58]. Tan et al [59] revealed that the topical application of Vicenin-2 film which is a type of flavonoid-derived glycosides from various natural plants can reduce blood-glucose levels in diabetic mice. Hence, that, lowering blood-glucose levels on diabetic mice can be influenced by topical treatment of open wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The ointment formula contains flavonoids could be released into wounds and then to the bloodstream so as to induce secretion of cytokine, growth factor and increase insulin production or insulin sensitivity of somatic cells. Flavonoids also cause re-formation of antioxidants and serum lipid profiles in diabetic rats [59]. The wound healing activity of the okra fruit extract topically on open wounds effectively forms the complete epithelization on 15 day [72] and achieves a complete epithelization on 16 day [73].…”
Section: Discussionmentioning
confidence: 99%